Challenges and Facilitators Influencing Physical Activity and Sedentary Behaviour Among South Asian Migrant Women in New Zealand - Silva, Wasani (Auckland University of Technology, 2016)
This qualitative descriptive study was conducted to fill the knowledge gap identified in the past literature by answering the research question, what are the challenges and facilitators influencing physical activity and sedentary lifestyle among South Asian migrant women in New Zealand? From the study findings, it is evident that the study has accomplished its goal as a number of challenges and facilitators to physical activity and sedentary lifestyle particularly relevant to the New Zealand environment were revealed. The study also presents an in-depth discussion of the findings, introducing suggestions to overcome the identified challenges and to strengthen the recognised facilitators. A need for culturally and gender-appropriate public health policies to improve the engagement of physical activity among South Asian migrant women in New Zealand, which may ultimately aid in reducing the burden of lifestyle diseases, was highlighted. Every possible step was taken to ensure the trustworthiness of this research project. With all the strengths of the study, few limitations were are also noted. Finally, this study can be seen as drawing the attention of New Zealanders to public health issues among minority women.
Keywords: Physical activity; Sedentary behaviour; South Asian migrant women in New Zealand; Challenges and facilitators; Qualitative descriptive